EVALUATION OF ANTIOXIDANT PROPERTIES OF Cucumis melo L cv. Hikapel DURING STORAGE AT ROOM TEMPERATURE - Puji Wulandari; Supriyadi Supriyadi; Budi Setiadi Daryono (University of Sultan Ageng Tirtayasa, 2019)
The changes in antioxidant compounds and antioxidant activities of melon (Cucumis Melo L.) cultivar Hikapel during postharvest storage at room temperature were evaluated. Melon with three ripening stages (27 DAA, 29 DAA, and 32 DAA) were harvested and stored at 25oC for 20 days. Melon cv. Hikapel were evaluated for their antioxidant compounds such as ascorbic acid, total phenolic (TPC), and total flavonoid content (TFC). Antioxidant capacity was also evaluated using DPPH radical scavenging assay (DPPH-RSA) and ferric reducing power assay (FRPA). The result showed that there were different levels of antioxidant compounds (TPC, TFC, and AAC) and antioxidant activities (DPPH-RSA & FRPA) in different ripening stages of this melon. Antioxidant compounds and antioxidant activity decreased during postharvest storage. In conclusion, melon cv. Hikapel provides various natural antioxidant compounds such as phenolic, flavonoid which can be the main contributors to the overall antioxidant activity of melon cv. Hikapel and its antioxidant properties were influenced by the postharvest storage period.